2017
DOI: 10.1097/brs.0000000000001862
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Results and Clinical Patient Outcome After Implantation of a Hydraulic Expandable Vertebral Body Replacement following Traumatic Vertebral Fractures in the Thoracic and Lumbar Spine

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
4
6
0
Order By: Relevance
“…Schnake et al reported an average ODI score of 12 points (=24.0%) at a five-year follow-up after posterior-anterior stabilization of traumatic thoraco-lumbar fractures using expandable titanium cages, which is also consistent with our results, nearly 9 years after surgery in average [ 10 ]. In line with our findings, Kreinest et al reported most patients to be satisfied, 3 years after implantation of a hydraulic expandable VBR following traumatic thoracic and lumbar vertebral fractures [ 11 ]. Different to our methods they chose the VAS Spine score as an outcome parameter and found a mean rating of 65.2 ± 23.1 in their study population, which was found to be comparable to the rating of 58.4 from the German Spine Fracture Registry for operatively treated patients after spine fractures [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Schnake et al reported an average ODI score of 12 points (=24.0%) at a five-year follow-up after posterior-anterior stabilization of traumatic thoraco-lumbar fractures using expandable titanium cages, which is also consistent with our results, nearly 9 years after surgery in average [ 10 ]. In line with our findings, Kreinest et al reported most patients to be satisfied, 3 years after implantation of a hydraulic expandable VBR following traumatic thoracic and lumbar vertebral fractures [ 11 ]. Different to our methods they chose the VAS Spine score as an outcome parameter and found a mean rating of 65.2 ± 23.1 in their study population, which was found to be comparable to the rating of 58.4 from the German Spine Fracture Registry for operatively treated patients after spine fractures [ 4 ].…”
Section: Discussionsupporting
confidence: 92%
“…Different to our methods they chose the VAS Spine score as an outcome parameter and found a mean rating of 65.2 ± 23.1 in their study population, which was found to be comparable to the rating of 58.4 from the German Spine Fracture Registry for operatively treated patients after spine fractures [ 4 ]. Comparable with our findings, they observed a significant reduction of functional outcome scores in their study cohort when compared to healthy subjects, but most of the patients (85.1%) were “generally/very satisfied” with their outcome [ 11 ]. Other study-groups like Spiegl et al achieved better VAS Scores with a thoracoscopic procedure [ 30 ], but in the current study we could not identify a significant influence of the surgical approach or other surgery-related parameters on the health-related QoL.…”
Section: Discussionsupporting
confidence: 87%
“…The mean rating of the VAS Spine score of their study population was 65.2 ± 23.1, which was found to be comparable to the rating of 58.4 from the German Spine Fracture Registry for operatively treated patients after spine fractures (4). Like our ndings, they saw a signi cant reduction of functional outcome scores in their study cohort when compared to healthy subjects (8). Indeed, other study-groups like Spiegl et al achieved better VAS Scores with a thoracoscopic procedure (24), but in the current study we could not identify a signi cant in uence of the surgical approach or other surgeryrelated parameters on the PROM.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the ODI outcome only one patient reported crippling back pain and no patient suffered exacerbated back pain or was bed-bound. (8). The mean rating of the VAS Spine score of their study population was 65.2 ± 23.1, which was found to be comparable to the rating of 58.4 from the German Spine Fracture Registry for operatively treated patients after spine fractures (4).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation